Seeds of sustainability : (Island Press, 2011)
Seeds of Sustainability is a groundbreaking analysis of agricultural development and transitions toward more sustainable management in one region. An invaluable resource for researchers, policymakers, and students alike, it examines new approaches to make agricultural landscapes healthier for both the environment and people.